1982
DOI: 10.1002/pen.760220402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight and molecular weight distribution on mechanical properties of polymers

Abstract: This work reviews the literature published over the last ten years on polymer mechanical properties as a function of molecular weight and molecular weight distribution, Thermal properties, stress‐strain properties, impact, fracture, fatigue, creep, stress relaxation and cracking and crazing are examined for a wide variety of homopolymers and a limited number of copolymers. In general, mechanical properties increase as the molecular weight increases. However, above some limiting molecular weight the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
231
0
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(264 citation statements)
references
References 119 publications
10
231
0
10
Order By: Relevance
“…The modulus of a polymer is not strongly affected by molecular weight but is predominantly a function of the crystallinity. Increased crystallinity is associated with increased stiffness, however the work of Margolies(in 27 ) shows that increasing the molecular weight of linear polymers results in a deterioration in the crystallinity, and hence the stiffness of the polymer. The decrease in flexural stiffness reaches a critical point around a molecular weight of 1.75 x 10 6 , above which no further significant decrease in evident The work of Phillips and co-workers( 2 0) showed that in the absence of orientation, an increase in flexural modulus can be attributed to enhanced crystallinity.…”
Section: L_mentioning
confidence: 99%
“…The modulus of a polymer is not strongly affected by molecular weight but is predominantly a function of the crystallinity. Increased crystallinity is associated with increased stiffness, however the work of Margolies(in 27 ) shows that increasing the molecular weight of linear polymers results in a deterioration in the crystallinity, and hence the stiffness of the polymer. The decrease in flexural stiffness reaches a critical point around a molecular weight of 1.75 x 10 6 , above which no further significant decrease in evident The work of Phillips and co-workers( 2 0) showed that in the absence of orientation, an increase in flexural modulus can be attributed to enhanced crystallinity.…”
Section: L_mentioning
confidence: 99%
“…In the proposed model (Equation 4), the stiffness decreases as the fluidity index increases; this is in accordance to literature data for samples that doesn't present high degree of orientation. Kundu et al 6 found an inverse correlation between modulus and MW for polyethylene. Stiffness = a * FI + b * density + c (4) Latado et al 3 tested many grades of polypropylene and propylene/ ethylene copolymers to develop empirical models in order to predict the stiffness.…”
Section: Uts = a * 1n(fi) + B (1)mentioning
confidence: 99%
“…Kundu et al 6 showed the influence of various film preparation procedures on the crystallinity, morphology and mechanical properties of pure linear low density polyethylene. According to them, quenching of films reduces the degree of cristallinity whereas natural cooling allows crystals to grow to a stacked lamellar structure or to a higher spherulite embedded in lamellar structure and hence increases in cristallinity.…”
Section: Uts = a * 1n(fi) + B (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] The optical band gap (E opt g ) of conjugated polymers typically saturate already at low P n , 26,27 the excellent physical properties associated with commodity plastics (such as mechanical compliance and durability), however, are significantly affected by molecular weight. 28,29 Unfortunately, despite numerous optimizations of the polycondensation reaction to synthesize CPIs based on PFK, molecular weights remained relatively low (P n ∼ 9). 9 To address this shortcoming, we set out to optimize the polymerization conditions in order to synthesize higher molecular weight cross-conjugated aromatic polyketones with potentially interesting optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%